(untitled) (Intent Research Scientific Journal, 2023)
The main objective of this scientific research is to compare the roots and roots of wild sugar reeds growing in the biotopes of the Valley of Zarephath to the nematodafaun of trees (black tomatoes) growing in this biotope, comparing the similarity levels. Also, when we compared the nematodes that we encountered in the soil of the root and the root atrophy of these plants, it turned out that there is a big difference between them from each other. The results were calculated by the Mauntford generality indicator.